Returning to Judgment Bernard Stiegler and Continental Political Theory. - Turner, Ben (SUNY Series in Contemporary Continental Philosophy Ser., 2023)
Explores the importance of political judgment in the work of Bernard Stiegler, and argues his approach to judgment marks an important break with continental political thought.